A percepção de jovens da geração digital quanto ao suporte ao trabalho oferecido pela organização - Pinho, Magda Sales (2014)
In the organizational environment, social changes caused by access to Information Technology resources influence the production processes, specifically in the form of work and the way of seeing and interpreting work. The entry of young people into the labor market has presented a scenario of instability, dissatisfaction, and new behaviors in the procedures proposed by organizations that expect more commitment by the young employees. Currently, young people seek personal job satisfaction, self-realization, and recognition, which were less frequent behaviors in earlier generations (Twenge, 2010). The literature reports that these young people are creative, ambitious, and interested in people and groups (Tapscott, 2010). According to some authors, relational bonds (Eisner, 2005) and the role of leadership (Lipkin; Perrymore, 2009) have emerged as key factors for the stability of the young in the organization. This study aims to identify the perception of the young, digital generation on the support work offered by the organization. For that, the constructs of Perceived Organizational Support (POS) and Perceived Social Support (PSS) were studied. In this research a survey was used, replicating the questionnaires by Siqueira (2009). The study sample was composed of young, lower middle class, college students, who already work or have professional experience. The data collected in the survey were tabulated and processed by the PLS software. The Organizational Support construct was altered to identify variables that relate to the welfare of the employee, job satisfaction, the physical and environmental conditions of work, and the company's availability to assist the employee in case of need. The construct Social Support, the factor about the perception of the young regarding communication, was kept with just a small adjustment. The proposed changes in the organization of the Social Support construct suggest that respondents are less concerned about the factors that involve relationships with team members and the resources offered by companies for development of the work, and more concerned with information and communication. These areas are significant and valued factors by young people in their working environment.